Isotopic discrimination of stable isotopes of nitrogen (δ15N) and carbon (δ13C) in a host-specific holocephalan tapeworm. Issue 3 (September 2014) - Navarro, J.; Albo-Puigserver, M.; Coll, M.; Saez, R.; Forero, M.G.; Kutcha, R.
Abstract During the past decade, parasites have been considered important components of their ecosystems since they can modify food-web structures and functioning. One constraint to the inclusion of parasites in food-web models is the scarcity of available information on their feeding habits and host–parasite relationships. The stable isotope approach is suggested as a useful methodology to determine the trophic position and feeding habits of parasites. However, the isotopic approach is limited by the lack of information on the isotopic discrimination (ID) values of parasites, which is pivotal to avoiding the biased interpretation of isotopic results. In the present study we aimed to provide the first ID values of δ15N and δ13C between the gyrocotylidean tapeworm Gyrocotyle urna and its definitive host, the holocephalan Chimaera monstrosa. We also test the effect of host body size (body length and body mass) and sex of the host on the ID values. Finally, we illustrate how the trophic relationships of the fish host C. monstrosa and the tapeworm G. urna could vary relative to ID values. Similar to other studies with parasites, the ID values of the parasite–host system were negative for both isotopic values of N (Δδ15N = − 3.33 ± 0.63‰) and C (Δδ13C = − 1.32 ± 0.65‰), independent of the sex and size of the host. By comparing the specific ID obtained here with ID from other studies, we illustrate the importance of using specific ID in parasite–host systems to avoid potential errors in the interpretation of the results when surrogate values from similar systems or organisms are used.